Un estudio transcultural del prejuicio contra habitantes de calle con creacíon de medidas explícitas e implícitas - Silva, Carlos José Nieto (2016)
The objectives of this research were to create explicit and implicit measures of prejudice against homeless, and to identify factors associated with negative attitudes toward this population. To meet these objectives several studies collected in four articles were made. In the first article the literature on prejudice against homeless was reviewed. In this study was found that both, in Latin America and in the countries of industrialized West, have been reported stereotypes towards this population related to mental illness and drug addiction, as well as acts of discrimination related to limitations in the use of public space. Article two corresponded to a study of cross-cultural creation and validation of a scale of prejudice against homeless, created with basics of Item Response Theory and the Allport's scale of prejudice. The created scale presented evidence of construct validity, convergent validity and good internal consistency. It was also verified, in part, the Allport's theory of the scale of prejudice. The third article aimed at identifying factors associated with prejudice against homeless, and to build and test a hierarchical model to explain variations in the levels of this prejudice. The proposed model had four levels of prejudice mediations, good fit indices, and included the variables social dominance orientation, basic values, egocentrism, perception of insecurity and quality of contact with homeless people. In the fourth article was described the process of creating an implicit association test about attitudes toward homeless, and was tested scores correlation levels acquired with this test and those acquired with the scale established in article two. The results indicated that there are strong associations between concepts representing the homeless people and negative stereotypes towards this population. No correlation between the scores on the two measures was found, in line with other studies on implicit and explicit measures of stereotypes.